PENGARUH AUDIT TENURE , REPUTASI KAP, DISCLOSURE,UKURAN PERUSAHAAN DAN PROFITABILITAS TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR PADA BURSA EFEK INDONESIA (BEI) TAHUN 2011-2015 - Okkidaya Prima Putra; Harun Delamat; Relasari Relasari (AKUNTABILITAS, 2016)
This research is to check the effect of audit tenure, accounting firm reputation, disclosure, company size, and prior year audit opinion to going concern audit opinion. This research was using samples of manufacturing industry. They were listed on the Indonesian Stock Exchange in 2011-2015. Based on method purposive sampling, research samples total are 80 financial statements. Hypothesis in this research used logistic regression.This research indicated that profitability had significant effect on the going concern audit opinion. Profitability had significant value of 0,036 below 0,05. Audit tenure, accounting firm reputation, disclosure and company size did not have significant effect on the going concern audit opinion.